2002
DOI: 10.1016/s1388-9842(02)00113-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nebivolol on left ventricular function in patients with chronic heart failure: a pilot study

Abstract: Background: Sympathetic activity is a significant predictor of a poor prognosis in heart failure. Beta-blockers have been shown to improve the prognosis of patients with heart failure. Aim: This pilot study examined the tolerability and efficacy of the new b-blocker nebivolol on left ventricular function in patients with chronic heart failure. Methods and Results: Twelve patients with an ejection fraction of 13-39% were included in this double blind, placebo-controlled randomized trial of nebivolol administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
0
14
0
2
Order By: Relevance
“…In the trial conducted by Wisenbaugh et al, 16 two patients withdrew due to new or worsening diabetes mellitus, but there were few reported adverse events and no admissions for worsened heart failure during the three-month study. Similarly, Brehm et al 17 reported no serious clinical adverse events, including significant bradycardia and hypotension, and no patients experienced deterioration in cardiac function. In both trials comparing nebivolol with carvedilol, reported adverse events were similar between treatment groups, with 63% of patients receiving nebivolol reaching the target dosage of 5 mg daily in one study, while 83% reached the same target dosage in the other trial.…”
Section: Safetymentioning
confidence: 83%
See 1 more Smart Citation
“…In the trial conducted by Wisenbaugh et al, 16 two patients withdrew due to new or worsening diabetes mellitus, but there were few reported adverse events and no admissions for worsened heart failure during the three-month study. Similarly, Brehm et al 17 reported no serious clinical adverse events, including significant bradycardia and hypotension, and no patients experienced deterioration in cardiac function. In both trials comparing nebivolol with carvedilol, reported adverse events were similar between treatment groups, with 63% of patients receiving nebivolol reaching the target dosage of 5 mg daily in one study, while 83% reached the same target dosage in the other trial.…”
Section: Safetymentioning
confidence: 83%
“…Brehm et al Brehm et al 17 conducted a similar trial examining the tolerability and efficacy of nebivolol on left ventricular function. Twelve patients with stable NYHA functional class III heart failure and an LVEF of ≤39% (mean, 29.7%) and receiving an ACE inhibitor, a diuretic, and digoxin were randomized to receive either nebivolol 2.5 mg daily or placebo; after 2 weeks, the daily dose of nebivolol was increased to 5 mg and continued for an additional 10 weeks.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…In most of these studies nebivolol was administered at a dosage of 5 mg, both in HF of ischemic origin and idiopathic dilated cardiomyopathy [57][58][59][60][61][62][63]. Apart from reducing HR and BP, it also showed an increase in LVEF [59][60][61][62][63][64], an enhancement of myocardial contractility [57,59] and improvement in coronary flow reserve [63]. Contradictory data are available about the effect of nebivolol on exercise capacity [60,62].…”
Section: Phase II Trialsmentioning
confidence: 99%
“…Brehm et al examined the tolerability and efficacy of nebivolol (2.5 or 5 mg) on left ventricular function in 12 patients with CHF [41]. LVEF increased (from 31 to 42%) and the left ventricular (LV) end-systolic diameter decreased after 12 weeks of nebivolol treatment.…”
Section: Clinical Trials In Heart Failurementioning
confidence: 99%